Different Predictors Shape the Diversity Patterns of Epiphytic and Non-epiphytic Liverworts in Montane Forests of Uganda - Maul, Karola; Wei, Yu-Mei; Nebel, Martin; Luebert, Federico; Ho, Boon-Chuan; Quandt, Dietmar; Kessler, Michael (Frontiers in Plant Science, 2020)
We studied the influence of regional and local variables on the liverwort diversity within natural forest vegetation of Uganda to contribute to our understanding of the mechanisms and processes determining species richness. To this end, we compared the species richness distribution patterns of epiphytic and non-epiphytic liverworts (Marchantiophytina) in 24 plots in the forests of four Ugandan national parks. We recorded a total of 119 species and subspecies from 18 families, including 16 new species records for the country. We used generalized linear models (GLMs) and the relative variable importance of regional and local climatic and environmental variables to assess their respective impact on the species diversity. We found that the richness patterns of total and epiphytic richness were largely driven by regional climatic factors related to temperature and water-availability. In contrast, species diversity of non epiphytic and rare species was additionally strongly determined by local-scale microhabitat factors such as height of forest canopy and slope inclination, reflecting the availability of suitable microhabitats. We conclude that macroclimatic variables perform well in predicting epiphytic liverwort richness, whereas the adequate prediction of non-epiphytic richness requires site specific variables. Also, we propose that richness of epiphytic liverworts will be impacted more directly by climate change than richness of non-epiphytic and rare species.